DNA Barcoding Diatoms From China With Multiple Genes - Zou, Shanmei; Bao, Yachao; Wu, Xuemin; Wang, Changhai (Frontiers in Marine Science, 2021)
Diatoms play a key role in water quality assessments and algae bloom. However, taxonomic confusion often exists for diatoms, and morphological characters are extremely diverse for species identification. DNA barcoding with multiple genetic markers can contribute much to diatom diversity investigation. In this study, we employed sequences of four genetic markers (COI, rbcL, SSU, and LSU) to discriminate diatom strains from both marine and freshwater environments of China, by tree, distance, and character-based barcoding methods. The available published diatom sequences were also incorporated into our new sequences. A total of 93 rbcL, 81 COI, 83 SSU, and 75 LSU sequences of diatom samples were obtained in this study. The multiple genetic markers discriminated most species clearly. The identification of species by micrographic observation was generally consistent with the DNA barcoding analysis except that some potential cryptic species were revealed by DNA barcoding. The COI, rbcL, and LSU sequences all showed high taxonomic resolution at the species level by phylogenetic and character-based analysis. Some potential identification errors in public diatom sequences were also found. The phylogenetic and character-based analysis revealed consistent species identification and showed clearer species discrimination than the distance-based method. In conclusion, our study evaluated the efficiency of four genetic markers in barcoding 11 genera within Bacillariophyta isolated from China and complemented many diatom reference sequences to public databases.